Kelestarian dalam pembangunan hartanah : faktor-faktor cabaran dan batasan terhadap praktis konsep bangunan hijau - Mohd Nazaruddin Yusoff @ Abdul Rahman (School of Environmental Engineering, University Malaysia Perlis, 2011)
This exploratory study aims to investigate the prima facie conjecture that there are barriers to the effective inculcation and practice of sustainability concept and green building elements among the main players in prorperty development in the states of Perlis, Kedah and Penang. These barrier may well be reasons for the main players to be less responsive to such inculcation and practice.